Stable isotopes of landfast sea ice as a record of La Grande River under-ice plume dispersal - Aura Diaz; Zou Zou A. Kuzyk; Alessia Guzzi; Kaushik Gupta; Tim Papakyriakou; Jens K. Ehn (Arctic Science)
Vertical profiles of salinity, and isotopic abundance ratios of hydrogen (δ2H) and oxygen (δ18O) of 18 landfast ice cores, collected along the northeast coast of James Bay in March 2019, and one ice core collected in Belcher Islands, were used to obtain the winter timeseries of the spatiotemporal evolution of the under-ice plume of La Grande River (LGR), the dominant river in the area. Variability in the isotopic composition and salinity of the ice cores indicated changes to the water source composition at the ice–water interface when the ice layers formed. The increased presence of river water beneath the ice during January–March was marked by more negative isotopic ratios in the lower portion of the ice as river discharge was increased for hydroelectric production. River water was the source of ∼43% of the ice in our ice core samples (n = 320) with the interquartile range from 16% to 71%. The river water fractions incorporated into the ice indicate that LGR under-ice plume extended more than 75 km north and at least 30 km south of the river mouth for ∼3 months. These findings correspond well with more challenging to obtain hydrographic observations. End-of-winter ice core sampling and analysis for isotopic abundance has potential as a tool to monitor dispersal of LGR discharge into the ice-covered coastal environment.